Positive electrode active material for rechargeable batteries

JP7641385B2Active Publication Date: 2025-03-06UMICORE(BE)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023537161
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-18
Filing Date
2021-12-17
Publication Date
2025-03-06
Estimated Expiration
2041-12-17

Smart Images

  • Figure 0007641385000002
    Figure 0007641385000002
  • Figure 0007641385000001
    Figure 0007641385000001
Patent Text Reader

Abstract

1. A positive electrode active material for an all-solid-state rechargeable battery, the positive electrode active material being a powder comprising Li, M', and O, wherein M' is composed of Co at a content x of 2.0 mol % to 35.0 mol %, Mn at a content y of 0 mol % to 35.0 mol %, A at a content m of 0 mol % to 5 mol %, A containing at least one element selected from the group consisting of Al, Ba, B, Mg, Nb, Sr, Ti, W, S, Ca, Cr, Zn, V, Y, Si, and Zr, and Ni at a content of (100-xym) mol %, the positive electrode active material further comprising a first compound comprising Li2WO4 and a second compound comprising WO3, the powder being a single crystal powder, the positive electrode active material comprising Li in a molar ratio of Li / (Co+Mn+Ni+A) that is at least 0.9 and at most 1.1, and the positive electrode active material having a tap density of at least 1.0 gr / cm 3 and a maximum of 3.0 g / cm 3 This is the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a particulate active cathode material for an all-solid-state rechargeable battery. More specifically, the present invention relates to a particulate active cathode material comprising tungsten oxide. [Background technology]

[0002] The applicability of conventional compounds as positive electrode active materials in all-solid-state batteries is limited due to their limited capacity retention after repeated charge-discharge cycling at high temperatures and voltages. Summary of the Invention [Problem to be solved by the invention]

[0003] The present invention provides improved stability and lower capacitance leakage (Q total The present invention aims to provide a method for producing a positive electrode active material having electrochemical properties such as: [Means for solving the problem]

[0004] The object is to provide a cathode active material for an all-solid-state battery, the cathode active material comprising Li, M', and O, wherein M' is Co with a content x of 2.0 mol % or more and 35.0 mol % or less relative to M'; Mn having a content y of 0 mol% or more and 35.0 mol% or less relative to M'; A having a content m of 0 mol % or more and 5 mol % or less with respect to M', which contains at least one element selected from the group consisting of Al, Ba, B, Mg, Nb, Sr, Ti, W, S, Ca, Cr, Zn, V, Y, Si, and Zr; (100-xym) mol % Ni, i. a first compound comprising Li2WO4; and ii. and a second compound comprising WO3; the powder is a single crystal powder, the positive electrode active material contains Li in a molar ratio of Li / (Co+Mn+Ni+A) of at least 0.9 and at most 1.1; The positive electrode active material is at least 1.0 gr / cm 3 And a maximum of 3.0g / cm 3 This is accomplished by providing a positive electrode active material having a tap density of

[0005] The present invention further provides an electrochemical cell comprising an active cathode material according to the first aspect of the invention, an all-solid-state battery comprising an active cathode material according to the first aspect of the invention, and the use of an active cathode material according to the first aspect of the invention in a battery.

[0006] For further guidance, figures are included to better understand the teachings of the present invention, which are intended to aid in the explanation of the invention and are not intended to limit the invention of this disclosure. [Brief description of the drawings]

[0007] [Figure 1] 1 shows an X-ray diffractogram of a positive electrode active material powder containing Li2WO4 and WO3 compounds by EX1.5, in which the horizontal axis shows the diffraction angle 2θ in degrees and the vertical axis shows the signal intensity on a logarithmic scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Unless otherwise defined, all terms used in disclosing the present invention, including technical and scientific terms, have the meanings commonly understood by those skilled in the art to which the present invention belongs. With further guidance, definitions of terms are included to better understand the teachings of the present invention. As used herein, the following terms have the following meanings: As used herein, "about" referring to a measurable value such as a parameter, amount, length of time, and the like, is meant to encompass a variation of no more than ±20%, preferably no more than ±10%, more preferably no more than ±5%, even more preferably no more than ±1%, and even more preferably no more than ±0.1% from the specified value, provided such variations are appropriate for the practice of the disclosed invention, although it is to be understood that the value to which the "about" modifier refers is itself specifically disclosed.

[0009] The recitation of numerical ranges by endpoints includes all values ​​and fractions subsumed within that range as well as the recited endpoints. All percentages are to be understood as percentages by weight, abbreviated as "wt. %," unless otherwise defined or a different meaning is apparent to one of ordinary skill in the art from its usage and in the context in which it is used.

[0010] As used herein, D50 is defined as the particle size at 50% of the cumulative volume percent distribution of the positive electrode active material powder, which can be determined by laser diffraction particle size distribution analysis.

[0011] positive electrode active material In a first aspect, the present invention provides an active cathode material for an all-solid-state rechargeable battery, the active cathode material comprising Li, M′, and O, wherein M′ is Co with a content x of 2.0 mol % or more and 35.0 mol % or less relative to M'; Mn having a content y of 0 mol% or more and 35.0 mol% or less relative to M'; A having a content m of 0 mol % or more and 5 mol % or less with respect to M', which contains at least one element selected from the group consisting of Al, Ba, B, Mg, Nb, Sr, Ti, W, S, Ca, Cr, Zn, V, Y, Si, and Zr; M' is composed of (100-xym) mol % Ni, iii. a first compound comprising Li2WO4; and iv. A powder comprising a second compound comprising WO3; the powder is a single crystal powder, The cathode active material includes Li in a molar ratio of Li / (Co+Mn+Ni+A) of at least 0.9 and at most 1.1.

[0012] Preferably, the positive electrode active material is at least 1.0 gr / cm 3 And a maximum of 3.0g / cm 3 The tap density is

[0013] The single crystal powder has a size of at least 45 μm by at least 60 μm (i.e., at least 2700 μm) in the SEM image. 2 ), preferably at least 100 μm by at least 100 μm (i.e., at least 10,000 μm 2 ) is considered to be a powder in which 80% or more of the particles within the field of view have single crystal morphology.

[0014] A particle is considered to have single crystal morphology if it consists of only one grain or a very small number of constituent grains, up to a maximum of five, as viewed by SEM or TEM.

[0015] In determining the monocrystalline morphology of a particle, grains having a maximum linear dimension observed by SEM that is smaller than 20% of the median particle size D50 of the powder as determined by laser diffraction are ignored. This avoids inadvertently considering particles that are essentially monocrystalline but have several very small other grains deposited on them as not having monocrystalline morphology.

[0016] The inventors have found that the cathode active material for an all-solid-state battery according to the present invention can indeed achieve a higher DQ1 and a lower IRRQ, which is illustrated by the examples and the results shown in Table 2.

[0017] Preferably, the present invention provides a cathode active material according to a first aspect of the present invention, wherein the total tungsten content is at least 0.20% and / or at most 2.50% by weight, based on the total weight of the cathode active material, as determined by ICP-OES analysis, where ICP-OES means inductively coupled plasma optical emission spectroscopy. Preferably, the weight ratio is between 0.25% and 2.00% by weight, more preferably, the weight ratio is equal to 0.30, 0.50, 1.00, 1.50, 2.00, or any value therebetween.

[0018] The positive electrode active material is defined as a material that is electrochemically active in the positive electrode of a solid-state battery. An active material is understood to be a material that can capture and release Li-ions when exposed to a voltage change for a period of time.

[0019] The content of each element can be determined by a known analysis method such as inductively coupled plasma-optical emission spectrometry (ICP-OES).

[0020] The Ni content (100-xym) in the positive electrode active material is preferably ≧60 mol %, more preferably ≧65 mol %, relative to M′.

[0021] The Ni content (100-xym) in the positive electrode active material is preferably ≦95 mol %, more preferably ≦90 mol %, relative to M′.

[0022] The Mn content y in the positive electrode active material is preferably ≧0 mol %, more preferably ≧5 mol %, relative to M′.

[0023] The Mn content y in the positive electrode active material is preferably <35 mol %, more preferably ≦30 mol %, relative to M'.

[0024] The content x of Co in the positive electrode active material is preferably ≧2 mol %, more preferably ≧5 mol %, relative to M′.

[0025] The Co content x in the positive electrode active material is preferably ≦35 mol %, more preferably ≦30 mol %, relative to M′.

[0026] The content m of A in the positive electrode active material is preferably 0.01 mol % or more relative to M'.

[0027] The content m of A in the positive electrode active material is preferably 2.0 mol % or less relative to M'.

[0028] The tap density of the positive electrode active material is preferably at least 1.5 g / cm 3 , more preferably at least 1.7 g / cm 3 It is.

[0029] The tap density of the positive electrode active material is preferably at most 2.7 g / cm 3 , more preferably at most 2.5 g / cm 3 It is.

[0030] The tap density of the cathode active material of the present invention is the ratio of the weight of the powder (W in grams) to the final volume occupied by the powder (cm) after tapping a specified number of times, such as 5000 times. 3 The tap density is calculated as W / V.

[0031] First Compound and Second Compound Preferably, the present invention provides a cathode active material according to a first aspect of the present invention, wherein the first compound comprises Li2WO4 and belongs to space group R-3, and the second compound comprises WO3 and belongs to space group P21 / n, as determined by X-ray diffraction analysis.

[0032] Preferably, the present invention provides a cathode active material according to the first aspect of the present invention, wherein the total tungsten content, determined by ICP-OES analysis, is between 0.20% and 2.50% by weight, based on the total weight of the cathode active material. Preferably, the weight ratio is between 0.25% and 2.00% by weight, more preferably, the weight ratio is equal to 0.50, 1.00, 1.50, 2.00, or any value therebetween.

[0033] In a second aspect, the present invention provides a battery cell comprising an active cathode material according to the first aspect of the present invention.

[0034] In a third aspect, the present invention provides the use of the cathode active material according to the first aspect of the present invention in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system.

[0035] The third compound of lithium transition metal oxide Preferably, the present invention provides an active cathode material according to the first aspect of the present invention, wherein the active cathode material comprises a third compound belonging to the R-3m space group as determined by X-ray diffraction analysis.

[0036] Preferably, the third compound is a lithium transition metal oxide, i.e. Li-M'-oxide as defined herein above. The lithium transition metal oxide is identified by X-ray diffraction analysis. According to "Journal of Power Sources (2000), 90, 76-81", the lithium transition metal oxide has a crystal structure belonging to the R-3m space group.

[0037] Electrochemical Cell In a second aspect, the present invention provides an electrochemical cell comprising an active cathode material according to the first aspect of the invention, a lithium-ion rechargeable battery comprising a liquid electrolyte and an active cathode material according to the first aspect of the invention, and the use of an active cathode material according to the first aspect of the invention in any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system.

[0038] Method for preparing positive electrode active material Preferably, the present invention relates to a method for preparing a cathode active material according to the first aspect of the present invention as described herein above, the method comprising the steps of: mixing a powder of a single crystal lithium transition metal oxide with a W-containing compound to obtain a mixture; and heating the mixture in an oxidizing atmosphere at a temperature of 250° C. to 450° C. to obtain the positive electrode active material.

[0039] Preferably, the W-containing compound is WO3.

[0040] Preferably, the amount of W used in the process is 0.20% to 2.50% by weight based on the total weight of the cathode active material, as determined by ICP-OES analysis.

[0041] The mixture is preferably heated at a temperature of 300°C to 400°C, more preferably at a temperature of 325°C to 375°C.

[0042] Preferably, the heated powder and / or cathode material is further processed, for example by grinding and / or sieving.

[0043] Optionally, the lithium transition metal oxide comprises A, where A comprises at least one element selected from the group consisting of Al, Ba, B, Mg, Nb, Sr, Ti, W, S, Ca, Cr, Zn, V, Y, Si, and Zr. EXAMPLES

[0044] The following examples are intended to further clarify the invention, but are not intended to limit the scope of the invention.

[0045] 1. Description of analysis method 1.1.Inductively Coupled Plasma The composition of the positive electrode active material powder is measured by inductively coupled plasma (ICP) method using Agilent 720 ICP-OES (Agilent Technologies, https / www.agilent.com / cs / library / brochures / 5990-6497EN%20720-725_ICP-OES_LR.pdf). One gram of powder sample is dissolved in 50 mL of high-purity hydrochloric acid (at least 37 wt% HCl with respect to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with a watch glass and heated on a hot plate at 380 °C until the powder is completely dissolved. After cooling to room temperature, the solution from the Erlenmeyer flask is poured into a first 250 mL volumetric flask.

[0046] The first volumetric flask is then filled to the 250 mL mark with deionized water, followed by thorough homogenization (first dilution). An appropriate amount of solution is pipetted from the first volumetric flask and transferred to a second 250 mL volumetric flask for the second dilution, and the second volumetric flask is filled to the 250 mL mark with internal standard elements and 10% hydrochloric acid, followed by homogenization. Finally, this solution is used for ICP-OES measurement.

[0047] 1.2.Particle size distribution The particle size distribution (PSD) of the cathode active material powders is measured by laser diffraction particle size distribution analysis using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory (https: / / www.malvernpanalytical.com / en / products / product-range / mastersizer-range / mastersizer-3000#overview) by dispersing each powder sample in aqueous media. Sufficient sonication and agitation are applied and appropriate surfactants are introduced to improve the dispersion of the powders. D50 is defined as the particle size at 50% of the cumulative volume percent distribution obtained from the Malvern Mastersizer 3000 by Hydro MV measurements.

[0048] 1.3.X-ray diffraction X-ray diffraction patterns of the positive electrode active material are collected on a Rigaku X-Ray Diffractometer D / max2000 (Rigaku, Du, Y. et al. (2012). A general method for the large-scale synthesis of uniform ultrathin metal sulphide nanocrystals. Nature Communications, 3(1)) using a CuKα source (40 kV, 40 mA) emitting at a wavelength of 1.5418 Å. The instrument configuration is set to a 1° Soller slit (SS), a 10 mm divergence height limiting slit (DHLS), a 1° divergence slit (DS), and a 0.3 mm receiving slit (RS). The goniometer diameter is 185 mm. For XRD, diffraction patterns are obtained in the range of 15 to 70° (2θ) with a scan rate of 1° per minute and a step size of 0.02° per scan.

[0049] 1.4. Polymer cell test 1.4.1. Preparation of polymer cells 1.4.1.1. Preparation of Solid Polymer Electrolyte (SPE) The solid polymer electrolyte (SPE) is prepared according to the following method. Step 1) Prepare polyethylene oxide (PEO with a molecular weight of 1,000,000, Alfa Aesar) in 99.8 wt% anhydrous acetonitrile (Aldrich https: / / www.sigmaaldrich.com / catalog / product / sial / 271004?lang=ko&®ion=KR&gclid=EAI aIQobChMIwcrB0dDL6AIVBbeWch0ieAXREAAYASAAEgJCa_D_BwE) using a mixer at 2000 revolutions per minute (rpm) for 30 minutes. https: / / www.Alfa.co.kr / AlfaAesarApp / faces / adf.task-flow?adf.tfld=ProductDetailsTF&adf.tfDoc= / WEB-INF / ProductDetailsTF.xml&ProductId=043678&_afrLoop=1010520209597576&_afrWindowMode=0&_afrWindowId=null) is mixed with lithium bis(trifluoromethanesulfonyl)imide salt (LiTFSI, Soulbrain Co., Ltd.). The molar ratio of ethylene oxide to lithium is 20. Step 2) Pour the mixture from step 1) into a Teflon dish and dry at 25°C for 12 hours. Step 3) Remove the dried SPE from the dish and punch out the dried SPE to obtain an SPE disk with a thickness of 300 μm and a diameter of 19 mm.

[0050] 1.4.1.2. Preparation of the Positive Electrode The positive electrode is prepared according to the following method. Step 1) Prepare a polymer electrolyte mixture containing a solution of polycaprolactone (PCL with a molecular weight of 80,000, Sigma-Aldrich https: / / www.sigmaaldrich.com / catalog / product / sial / 296295) in 99.7 wt% anhydrous anisole (Sigma-Aldrich https: / / www.sigmaaldrich.com / catalog / product / aldrich / 440744) and bis(trifluoromethanesulfonyl)imide salt (LiTFSI, Sigma-Aldrich, https: / / www.sigmaaldrich.com / catalog / product / aldrich / 544094) in acetonitrile. The mixture has a weight ratio of PCL:LiTFSI of 74:26. Step 2) The polymer electrolyte mixture prepared in step 1), the positive electrode active material, and the conductive powder (Super P, Timcal (Imerys Graphite & Carbon), http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2018 / 10 / ENSACO-150-210-240-250-260-350-360-G-ENSACO-150-250-P-SUPER-P-SUPER-P-Li-C-NERGY-SUPER-C-45-65-T_V-2.2_-USA-SDS.pdf) are mixed in an acetonitrile solution in a weight ratio of 21:75:4 to prepare a slurry mixture. Mixing is performed by a homogenizer at 5000 rpm for 45 minutes. Step 3) Cast the slurry mixture of step 2) onto one side of a 20 μm thick aluminum foil with a coater gap of 100 μm. Step 4) The foil on which the slurry was cast is dried at 30° C. for 12 hours, and then punched out to obtain a positive electrode with a diameter of 14 mm.

[0051] 1.4.1.3. Polymer cell assembly Assemble a coin-shaped polymer cell in an argon-filled glove box from bottom to top: 2032 coin cell can, the positive electrode prepared in section 1.5.1.2, the SPE prepared in section 1.5.1.1, a gasket, a Li anode, a spacer, a wave spring, and a cell cap. The coin cell is then completely sealed to prevent electrolyte leakage.

[0052] Test Method Each coin polymer cell is cycle tested at 80 °C using a Toscat-3100 computer-controlled constant current cycling station (Toyo Systems, http: / / www.toyosystem.com / image / menu3 / toscat / TOSCAT-3100.pdf). The coin cell test procedure uses a 1C current definition of 160 mA / g in the 4.4-3.0 V / Li metal window range according to the schedule below. Step 1) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V, followed by a 10 minute rest. Step 2) Discharge in constant current mode at a C rate of 0.05 with an end condition of 3.0 V, followed by a 10 minute rest. Step 3) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V. Step 4) Switch to constant voltage mode and maintain 4.4V for 60 hours. Step 5) Discharge in constant current mode at a C rate of 0.05 with an end condition of 3.0V.

[0053] Q total Q is defined as the total leakage capacitance at high voltage and temperature in step 4) according to the described test method. total A small value of indicates that the positive electrode active material powder has high stability during high temperature operation.

[0054] 1.5.Tap Density The tap density of the positive electrode active material in the present invention is measured by mechanically tapping a 100 mL graduated cylinder containing the positive electrode active material. After observing the weight of the powder (W in grams), the graduated cylinder is mechanically tapped 5000 times to measure the final volume (cm) without observing any further volume change. 3 The tap density is calculated as W / V.

[0055] 2. Examples and Comparative Examples Comparative Example 1 A single crystal positive electrode active material, labeled CEX (Comparative) 1, is prepared according to the following steps. Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.86 Mn 0.07 Co 0.07 Nickel-based transition metal oxide hydroxide powder (TMH1) having the formula (I) is prepared by co-precipitation in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) Heating: The TMH1 prepared in step 1) is heated at 400° C. for 7 hours in an oxidizing atmosphere to obtain a heated powder. Step 3) First Mixing: The heated powder prepared in step 2) is mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal ratio of 0.96. Step 4) First Calcination: The first mixture of step 3) is calcined at 890°C for 11 hours in an oxidizing atmosphere to obtain a first calcined powder. Step 5) Wet bead milling: The first calcined powder of step 4) is bead milled in a solution containing 0.5 mol% Co relative to the total molar content of Ni, Mn, and Co in the first calcined powder, followed by filtering, drying, and sieving to obtain a milled powder. The weight ratio of solid to solution for bead milling is 6:4, and the bead milling is carried out for 20 minutes. Step 6) Second Mix: The milled powder of step 5) is mixed in an industrial blender with 1.5 mol % Co from Co3O4 and 7.5 mol % Li from LiOH, each with respect to the total molar content of Ni, Mn and Co in the milled powder, to obtain a second mixture. Step 7) Second calcination: The second mixture of step 6) is calcined at 760°C for 10 hours in an oxidizing atmosphere, followed by grinding and sieving to obtain the second calcined powder, labeled CEX1. The tap density of the powder of CEX1 is 2.1 g / cm 3 It is.

[0056] Example 1 EX (Example) 1.1 is prepared according to the following method. Step 1) Mix CEX1 with WO3 powder to obtain a mixture containing about 0.36 wt% tungsten based on the total weight of the mixture. Step 2) The mixture obtained in step 1) is heated in a furnace at 350° C. for 10 hours under a flow of an oxidizing atmosphere. Step 3) The heated product of step 2) is ground and sieved to obtain a powder labeled EX1.1.

[0057] EX1.2, EX1.3, EX1.4, and EX1.5 are prepared according to the same method as EX1.1, except that in step 1), CEX2 is mixed with WO3 powder to obtain mixtures containing about 0.43 wt.%, 0.48 wt.%, 0.75 wt.%, and 1.50 wt.% tungsten, respectively, based on the total weight of the mixture.

[0058] Table 1 summarizes the compositions of the examples and comparative examples and their corresponding electrochemical properties. After the introduction of W and the formation of Li2WO4 and WO3, Q total A significant improvement in is observed.

[0059] The particle size distribution of the products of the examples and comparative examples was determined by a Malvern Mastersizer 3000. All of these products have a median particle size D50 of 3.8-4.6 μm. The tap density of EX1.1 is 2.1 g / cm 3 It is.

[0060] Comparative Example 2 A single crystal positive electrode active material, labeled CEX5, is prepared according to the following steps. Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.68 Mn 0.20 Co 0.12 Nickel-based transition metal oxide hydroxide powder (TMH2) having the formula: is prepared by co-precipitation in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) First Mixing: TMH2 prepared in step 1) is mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal ratio of 0.97. Step 4) First calcination: The first mixture of step 2) is calcined in an oxidizing atmosphere at 920° C. for 10 hours to obtain a first calcined powder. Step 5) Jet milling: The first calcined powder of step 4) is jet milled to obtain a milled powder labeled CEX2.

[0061] Example 2 A single crystal positive electrode active material, labeled EX2, is prepared according to the following steps. Step 1) Mix CEX2 with WO3 powder to obtain a mixture containing about 0.45 wt. % tungsten based on the total weight of the mixture. Step 2) The mixture obtained in step 1) is heated in a furnace at 350° C. for 10 hours under a flow of an oxidizing atmosphere. Step 3) The heated product of step 2) is ground and sieved to obtain a powder labeled EX2.

[0062] [Table 1]

[0063] The tungsten phase was identified by X-ray diffraction analysis (diffractometry). Figure 1 shows the XRD pattern of EX1.5.

[0064] According to the Journal of Power Sources (2000), 90, 76-81, the XRD patterns show that EX1.5 is mainly formed from lithium transition metal oxide compounds. They are LiNi 0.86 Mn 0.07 Co 0.07 O2. EX1.5 exhibits the R-3m, R-3, and P21 / n phases, which are LiNi 0.86 Mn 0.07 Co 0.07 The results show that the heating temperature of 350° C. is suitable for producing the first and second compound phases according to the present invention.

[0065] When the above-mentioned R-3m phase, R-3 phase and P21 / n phase are present in the positive electrode active material, the electrochemical properties are improved.

[0066] The electrochemical properties were further characterized in polymer cells, and tungsten-containing EX1.1 to EX1.5 all exhibited lower Q values ​​than tungsten-free CEX1. total Similarly, EX2, which contains 67 mol% Ni and 0.45 wt% W, has a lower Q compared to CEX2, which contains the same Ni content. total Shows.

Claims

1. A cathode active material for an all-solid-state rechargeable battery, the cathode active material comprising Li, M', and O, wherein M' is Co with a content x of 2.0 mol % or more and 35.0 mol % or less relative to M'; Mn having a content y of 0 mol% or more and 35.0 mol% or less with respect to M'; A has a content m of 0 mol % or more and 5 mol % or less with respect to M', and contains at least one element selected from the group consisting of Al, Ba, B, Mg, Nb, Sr, Ti, W, S, Ca, Cr, Zn, V, Y, Si, and Zr; (100-x-y-m) mol% Ni content; The positive electrode active material is i. Li 2 WO 4 A first compound phase comprising: ii. WO 3 a second compound phase comprising The positive electrode active material is a single crystal powder, the positive electrode active material comprises Li in a molar ratio of Li / (Co+Mn+Ni+A) of at least 0.9 and at most 1.1; The positive electrode active material has a viscosity of at least 1.0 gr / cm 3 And a maximum of 3.0 g / cm 3 The positive electrode active material has a tap density of

2. 2. The positive electrode active material according to claim 1, wherein the first compound phase has a crystal structure belonging to space group R-3 and the second compound phase has a crystal structure belonging to space group P21 / n, as determined by X-ray diffraction analysis.

3. 10. The cathode active material of claim 1, wherein a total tungsten content is from 0.20 wt % to 2.50 wt %, based on the total weight of the cathode active material, as determined by ICP-OES analysis.

4. 4. The cathode active material of claim 1, wherein the total tungsten content is 0.30 wt.% to 2.00 wt.%, based on the total weight of the cathode active material, as determined by ICP-OES analysis.

5. The cathode active material of any one of claims 1 to 4, wherein the cathode active material has a median particle size D50 of 2 μm to 7 μm as determined by laser diffraction particle size distribution analysis.

6. The positive electrode active material according to any one of claims 1 to 5, wherein m is less than 2.0 mol% relative to M'.

7. The first compound phase is Li 2 WO 4 The positive electrode active material according to any one of claims 1 to 6.

8. The second compound phase is WO 3 The positive electrode active material according to any one of claims 1 to 7.

9. The positive electrode active material according to any one of claims 1 to 8, wherein the Ni content (100-x-y-m) is 60 mol % to 95 mol % relative to M'.

10. The tap density is 1.5 g / cm 3 ~2.7g / cm 3 The positive electrode active material according to any one of claims 1 to 9.

11. An all-solid-state battery comprising the positive electrode active material according to any one of claims 1 to 10.

12. A battery cell comprising the positive electrode active material according to any one of claims 1 to 10.

13. Use of the positive electrode active material according to any one of claims 1 to 10 in a battery of any one of a portable computer, a tablet, a mobile phone, an electric vehicle, and an energy storage system.

Citation Information

Patent Citations

  • Positive electrode material for lithium-ion batteries containing nickel-cobalt-manganese multi-element additives and method for manufacturing the same

    JP2012517675A

  • Apparatus for manufacturing composite active material powder and method for manufacturing composite active material powder

    JP2016225161A

  • Nickel-based cathode material for rechargeable type lithium ion battery

    JP2019021623A

  • Lithium ion battery positive electrode material and lithium ion battery

    JP2019021627A

  • Method for preparing of positive electrode active material for lithium secondary battery, positive electrode active material for lithium secondary battery thereby

    KR1020200031305A